Composted biogas residue and spent mushroom substrate as a growth medium for tomato and pepper seedlings. (15th June 2018) - Meng, Xingyao; Dai, Jiali; Zhang, Yue; Wang, Xiaofen; Zhu, Wanbin; Yuan, Xufeng; Yuan, Hongli; Cui, Zongjun
Abstract: A composted material derived from biogas production residues, spent mushroom substrate (SMS) and pig manure was evaluated as a partial or total replacement for peat in growth medium for tomato and pepper seedlings. Five different substrates were tested: T1, compost + perlite (5:1, v:v); T2, compost + peat + perlite (4:1:1, v:v:v); T3, compost + peat + perlite (2.5:2.5:1, v:v:v); T4, compost + peat + perlite (1:4:1, v:v:v); and CK, a commercial peat + perlite (5:1, v:v). The physical-chemical characteristics of the various media were analyzed, and the germination rate and morphological growth were also measured. Real-time Quantitative PCR (qPCR) was used to quantify Fusarium concentrations. The addition of compost to peat-based growth medium increased the pH, electrical conductivity, air porosity, bulk density, and nutrition (NPK), and decreased the water holding capacity and total porosity. The use of compost did not affect the percent germination at day 15 of the tomato and pepper seedlings. The addition of compost resulted in better or comparable seedling quality compared with CK and fertilized CK. The best growth parameters were seen in tomato and pepper seedlings grown in T1 and T2, with higher morphological growth in comparison with CK and fertilized CK. However, T2 showed the highest Fusarium concentration compared to compost and all growth media. Fusarium concentrations in T1, T3, and T4 did not differ significantly from those in CK for tomato seedlings, and those in T1 and T4 were also similar to those in CK for pepper seedlings. The results suggest that biogas residues and SMS compost is a good alternative to peat, allowing 100% replacement, and that 20–50% replacement produces tomato and pepper seedlings with higher morphological growth and lower Fusarium concentrations. Highlights: Compost is a good media for the total or partial replacement of peat in seedlings. The addition of compost resulted in better or comparable seedling quality compared with CK and fertilized CK. The addition of compost did not increase the quantity of Fusarium except in pepper seedlings.